Effects of hydroxyapatite bovine tooth graft (HAp-BTG) and polyethylene glycol (PEG) combinations in post extraction sockets on the amount of osteoid - Zubaidah, Nanik; Wulandini, Raden Ajeng; Sa'adah, Nur Hikmatus; Arrianti, Tyas Ramadhini; Pribadi, Nirawati (Universitas Airlangga, 2023)
Background: One of the actions in the field of tooth conservation such as hemisection can result in changes, especially in hard tissue due to the extraction of tooth roots and part of the tooth crown. After tooth extraction, socket wound healing will occur which ends with the process of osteogenesis. This process can reduce the dimensions of the socket due to alveolar bone resorption. Socket preservation can prevent dimension reduction and bone resorption to achieve maximum treatment results. The administration of Hydroxyapatite bovine tooth graft (HAp-BTG) into the post-extraction socket is expected to increase the formation of osteoid matrix which is important in the formation of new bone. Purpose: Proving the effect of adding a combination of HAp-BTG and PEG into the post-extraction socket on increasing the number of osteoid. Methods: 32 wistar rats were divided into control and treatment groups. Then the lower left incisor was extracted, the post-extraction socket was filled with PEG for the control group and a combination of HAp-BTG and PEG for the treatment group. On the 14th and 28th day the wistar rats were terminated and the mandibles were taken to make tissue preparations. HE staining was performed on the samples and observing the extent of the osteoid using a microscope with 400x magnification. Results: There was a significant difference between the control group and the treatment group on the 14th and 28th days. Conclusion: Administration of a combination of HAp-BTG and PEG into the post-extraction socket increased the number of osteoid on the 14th and 28th days.